40 THE NATURAL HISTORY OF CRYPTOGENIC CIRRHOSIS FOLLOWING ORTHOTOPIC LIVER TRANSPLANTATION: A HISTORICAL COHORT STUDY. (1st March 2005) - Abdelmalek, M. F.; Mudaliar, K.; Liu, C.; Reed, A. I.; Nelson, D. R.; Asal, N. R.; Stacpoole, P. W.
Abstract : Background: The natural history of cryptogenic cirrhosis (CC) following liver transplantation (LT) is not well defined. Emergence of nonalcoholic fatty liver disease (NAFLD) with steatosis, inflammation (NASH), and cirrhosis has been previously reported. Existing reports are limited by small sample size, lack of follow-up, and the absence of clinicopathologic correlation with the insulin resistance (IR) syndrome. Aim: To assess the prevalence, incidence, and risk factors associated with NAFLD in patients (pts) transplanted for CC. Methods: All pts with CC transplanted from 1991-2003 were evaluated. Clinical data and all protocol/indication liver biopsies were reviewed and graded for steatosis (0-3), inflammatory (NASH) activity (0-3), and fibrosis (0-4) by a single pathologist blinded to clinical data. Results: Clinical Data: LT for CC was performed for 90 of 832 (11%) adult LT pts, mean age 53 ± 12 yrs (range 21-69 yrs), 54% men, and follow-up of 81 ± 62 mo (range 0-170 mo). At LT, the prevalence of hepatoma was 4% and mean calculated MELD score was 16.4 ± 6.2 (range 6-33). Survival: One and five-yr pt survival were 88% and 85% respectively. Repeat LT was required for 4 of 90 (4%). Cardiovascular disease (CVD) deaths occurred in 11 of 27 (41%) pts, 5 (55%) of which were within one yr of LT. Metabolic Parameters: IR was noted in 52% of pts pre-LT. During follow-up, no change was noted in weight, BMI, or glycemic control when compared to pre-LT values (p = ns). During the follow-up period, triglycerides, total and LDL cholesterol increased (p<0.01) and HDL cholesterol declined (p<0.01). Histology: At LT, grade 1 and 2 steatosis were noted in 39% and 6% respectively. At 1, 3, and 5 yrs post-LT, steatosis grade ≥ 1 was noted in 39%, 76%, and 89%; steatosis ≥ grade 2 was noted in 11%, 69% and 71% of pts respectively. Mean steatosis grade was 0.91 ± 0.9, 0.96 ± 0.87, and 1.46 ± 0.96 (p<0.01). Mild NASH was observed in 1/3 of pts and did not increase over time. Comparable NASH grade was 1.06 ± 0.59, 0.68 ± 0.71, and 0.66 ± 0.89 (p<0.05), and fibrosis from 1.09 ± 1.15, 1.0 ± 0.97, and 1.5 ± 1.3 (p<ns). One pt developed cirrhosis by 5 yr post-LT. Conclusions: NAFLD is a common sequela for pts undergoing LT for CC. Progression to advanced fibrosis was uncommon in this cohort and survival is excellent. IR is present in a majority of patients with CC with CVD is the leading cause of mortality post LT. Hyperlipidemia primarily correlates with recurrent NAFLD post-LT.